Pengaruh Minat Belajar Terhadap Hasil Belajar Siswa Kelas XI pada Mata Pelajaran Ekonomi di SMA Negeri 1 Sawan Tahun Ajaran 2021/2022 - Putra, I Nengah Jaya Oka Di (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the effect of learning interest on the learning outcomes of class XI students in economics at SMA Negeri 1 Sawan for the academic year 2021/2022. This type of research is using causal research. The population in this study were all students of class XI at SMAN 1 Sawan, where the total population of class XI at SMAN 1 Sawan was 202 people. Sampling using the Proportional Random Sampling technique, from Slovin's calculations, the number of respondents was 134 people. The data collection method used in this research is in the form of a questionnaire. The data obtained in the form of the results of a questionnaire containing the student's response to interest in learning with a Likert scale. In this study, we used simple regression analysis and hypothesis testing. Simple Regression Analysis, Y = a + bX. The results showed that there was a positive and significant influence on the learning interest of a class XI IPS student on economic learning outcomes at SMAN 1 Sawan.